Semiflexible Polymer Enclosed in a 3D Compact Domain - Castro-Villarreal, Pavel; Ramírez, J. E. (Frontiers in Physics, 2021)
The conformational states of a semiflexible polymer enclosed in a volume V:=^3 are studied as stochastic realizations of paths using the stochastic curvature approach developed in [Rev. E 100, 012503 (2019)], in the regime whenever 3/_ p> 1, where _p is the persistence length. The cases of a semiflexible polymer enclosed in a cube and sphere are considered. In these cases, we explore the Spakowitz-Wang type polymer shape transition, where the critical persistence length distinguishes between an oscillating and a monotonic phase at the level of the mean-square end-to-end distance. This shape transition provides evidence of a universal signature of the behavior of a semiflexible polymer confined in a compact domain.